In vitro Evaluation of Isoniazid Derivatives as Potential Agents Against Drug-Resistant Tuberculosis - Marquês, Joaquim Trigo; Frazão De Faria, Catarina; Reis, Marina; Machado, Diana; Santos, Susana; Santos, Maria da Soledade; Viveiros, Miguel; Martins, Filomena; De Almeida, Rodrigo F. M. (Frontiers in Pharmacology, 2022)
The upsurge of multidrug-resistant tuberculosis has toughened the challenge to put an end to this epidemic by 2030. In 2020 the number of deaths attributed to tuberculosis increased as compared to 2019 and newly identified multidrug-resistant tuberculosis cases have been stably close to 3 %. Such a context stimulated the search for new and more efficient antitubercular compounds, which culminated in the QSAR-oriented design and synthesis of a series of isoniazid derivatives active against Mycobacterium tuberculosis. From these, some prospective isonicotinoyl hydrazones and isonicotinoyl hydrazides are studied in this work. To evaluate if the chemical derivatizations are generating compounds with a good performance concerning several in vitro assays , their cytotoxicity against human liver HepG2 cells was determined and their ability to bind human serum albumin was thoroughly investigated. For the two new derivatives presented in this study, we also determined their lipophilicity and activity against both the wild type and an isoniazid-resistant strain of Mycobacterium tuberculosis carrying the most prevalent mutation on the katG gene, S315T. All compounds were less cytotoxic than many drugs in clinical use with IC50 values after a 72 h challenge always higher than 25 µM. Additionally, all isoniazid derivatives studied exhibited stronger binding to human serum albumin than isoniazid itself, with dissociation constants in the order of 10-4 – 10-5 M as opposed to 10-3, respectively. This suggests their transport and half-life in the blood stream are likely improved when compared to the parent compound. Furthermore, our results are a strong indication that the N’=C bond of the hydrazone derivatives of INH tested is essential for their enhanced activity against the mutant strain of M. tuberculosis in comparison to both their reduced counterparts and INH.